Corporate reporting on minority shareholders information and its implications on shareholders activism in Malaysia / Fazlina Mohd Fahmi and Normah Omar - Mohd Fahmi, Fazlina; Omar, Normah (Faculty of Accountancy, 2005)
The objectives of the current study are of two folds; dealing firstly with the commitment of the listed companies in reporting minority shareholders' information in their corporate annual report and secondly to determine the implication of such reporting practices towards shareholders activism in this country. It is implied in this study that if the reporting practices is fair and the level of shareholders activism is high, corporate governance practices could be significantly improved.